DENKER, A.; GROTH, M.; JENEWEIN, J.; ZABOROWSKI, H. (Editores), Heidegger und die Psychiatrie. Heidegger-Jahrbuch, Band 14. Baden-Baden: Verlag Karl Alber, 2023 - González Martínez, Ariadna Melina (Daimon Revista Internacional de Filosofia, 2025)
Reseña de DENKER, A.; GROTH, M.; JENEWEIN, J.; ZABOROWSKI, H. (Editores), Heidegger und die Psychiatrie. Heidegger-Jahrbuch, Band 14. Baden-Baden: Verlag Karl Alber, 2023